Pendidikan Kristen untuk Anak Usia Dini Dalam Mendukung Pembangunan Manusia Yang Berkelanjutan Melalui Pembelajaran Berkualitas - Suardin Zai (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2025)
Christian education for early childhood development plays a crucial role in shaping the moral, character, and intellectual development of children as the future generation. The purpose of this study is to analyze how Christian education for early childhood can contribute to sustainable human development through quality learning. The research employs a qualitative approach, utilizing literature reviews from books and journal articles. This study found that Christianity, guided by biblical values such as love, honesty, responsibility, and discipline, helps produce individuals with integrity, high social awareness, and the ability to adapt to globalization. Additionally, quality learning in Christian education provides optimal stimulation for the cognitive, emotional-social, and spiritual development of young children, which forms the foundation for sustainable human development. This research emphasizes that Christian education for young children requires constant innovation and improvement through a holistic approach to effectively respond to the challenges of the times and fulfill the goals of sustainable development.